THE IMPACT OF KINESIOTHERAPY IN THE RECOVERY OF ADOLESCENTS WITH SCOLIOSIS DEFICIENCY - D.A. SZABO; N. NEAGU; R.M. MUNTEANU; I.S. SOPA (Editura Universitatii Transilvania din Brasov, 2020)
The article focuses on two groups of children with scoliosis deficiency, first group, the experimental group, with whom we worked with kinesiotherapy programs and the second group, the control group, that work only with physiotherapy programs. The method used for assessing the scoliosis deficiency was the medical examination of specialists and the VAS questionnaire regarding pain level. The results showed statistically significant difference between the initial and final evaluation of scoliosis deficiency at the experimental group. Conclusions of the research proved that using specific kinesiotherapy programs can reduce pain level and correct scoliosis deficiency